A materials chemistry investigation of archaeological lead glazes - Walton, M (2004)
In this thesis, the fabrication technology of Roman lead glazes were examined using a number of materials science techniques: namely, electron probe microanalysis, X-ray diffraction, and inductively coupled plasma atomic emission spectroscopy. The overall aim of this work was to discern particular technological styles for a wide group of lead glazes by quantifying the chemical and microstructural features of glaze production. Using experimental replication, it was found that two basic methods of glazing could be identified chemically. When applying PbO alone to an earthenware ceramic, the resulting glaze was in equilibrium with the ceramic as indicated by flat compositional profiles obtained along the glaze cross-section. However, when applying PbO·SiO2 mixtures to earthenware ceramics, gradient profiles indicative of diffusive mass transfer were obtained from the glaze cross-section. On the basis of these chemical criteria, these two methods of glazing were identified in archaeological material. It has been determined that the earliest lead glazes from Anatolia and Italy (approximately 1st century B.C.) were made using PbO·SiO2 mixtures applied to calcareous clays with Fe and Cu oxides added as colourants. Later production (post 2nd century A.D.), seems to have employed PbO alone applied to non-calcareous clays with no intentionally added colourants. The Roman production of lead glazes was compared to both those of Late Antiquity (4th – 10th centuries A.D.) which continued to use PbO applied to non-calcareous clays, and to those of Byzantine and Islamic contexts (8th – 14th centuries A.D.) which seem to have used PbO·SiO2 mixtures applied to both calcareous and non-calcareous clays. It is also argued that the technological features of the Byzantine and Islamic glaze production shared more in common with the contemporary Chinese lead glazing tradition (the Sancai wares of the 7th century A.D.) which also used PbO·SiO2 mixtures applied to non-calcareous clays, than with the Late Antique glazing tradition.